2014
DOI: 10.1097/bcr.0000000000000011
|View full text |Cite
|
Sign up to set email alerts
|

Making Meaning in a Burn Peer Support Group

Abstract: There is a paucity of literature on the personal experiences of burn support group members, the members' perceived benefits of group participation, and the meaning the survivors make of the support they receive. In order to provide effective psychosocial rehabilitation services and to meet the needs of burn survivors, it is important to understand the influence a support group has on its members as well as the personal experiences of those individuals who attend these groups. The purpose of this study was to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Closely resonating with themes identified in our study, Davis et al’s 49 findings of six adult burn survivors in a Burn Peer Support Group setting identified a number of themes concerning the process of adjustment and meaning-making. In particular, “acceptance of self”, comprising also a self-narrative exploration aspect; “perspective change”, including hopefulness and the learning of new coping skills; “the value of community”, which broadly valued relationships; “reciprocity”, which involved aspects of altruism and providing support to others.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Closely resonating with themes identified in our study, Davis et al’s 49 findings of six adult burn survivors in a Burn Peer Support Group setting identified a number of themes concerning the process of adjustment and meaning-making. In particular, “acceptance of self”, comprising also a self-narrative exploration aspect; “perspective change”, including hopefulness and the learning of new coping skills; “the value of community”, which broadly valued relationships; “reciprocity”, which involved aspects of altruism and providing support to others.…”
Section: Discussionsupporting
confidence: 80%
“…In particular, “acceptance of self”, comprising also a self-narrative exploration aspect; “perspective change”, including hopefulness and the learning of new coping skills; “the value of community”, which broadly valued relationships; “reciprocity”, which involved aspects of altruism and providing support to others. Overall both Davis et al 49 and Kornhaber et al’s 39 findings suggest that participation in a Burn Peer Support Group had a perceived positive impact on psychosocial recovery, a task they described as the need to “integrate their injury into their identity within an encouraging and safe environment”. 49 The traumatic aspects of our participant’s experience echoes this need for integration.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Themes of psychological growth reported by support group members include acceptance of self, perspective change, value of community, and reciprocity [22]. The facilitation of community and development of relationships with other group members have also been reported as particularly useful benefits of participation.…”
Section: Discussionmentioning
confidence: 99%